2016
DOI: 10.1002/ece3.2185
|View full text |Cite
|
Sign up to set email alerts
|

The effect of diet and time after bacterial infection on fecundity, resistance, and tolerance in Drosophila melanogaster

Abstract: Mounting and maintaining an effective immune response in the face of infection can be costly. The outcome of infection depends on two host immune strategies: resistance and tolerance. Resistance limits pathogen load, while tolerance reduces the fitness impact of an infection. While resistance strategies are well studied, tolerance has received less attention, but is now considered to play a vital role in host–pathogen interactions in animals. A major challenge in ecoimmunology is to understand how some hosts m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

12
95
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 69 publications
(107 citation statements)
references
References 62 publications
12
95
0
Order By: Relevance
“…We used ten wild‐type populations. The locally collected population used in this study (1_4WS; Kutzer & Armitage, ) was maintained in a population cage with overlapping generations. Nine populations with variable fecundity (Ral208, Ral350, Ral367, Ral373, Ral375, Ral379, Ral406, Ral509 and Ral765) from the Drosophila Genetic Reference Panel (DGRP) originating from North Carolina, USA (Mackay et al ., ), were maintained in vials and placed onto new food every 2 weeks.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…We used ten wild‐type populations. The locally collected population used in this study (1_4WS; Kutzer & Armitage, ) was maintained in a population cage with overlapping generations. Nine populations with variable fecundity (Ral208, Ral350, Ral367, Ral373, Ral375, Ral379, Ral406, Ral509 and Ral765) from the Drosophila Genetic Reference Panel (DGRP) originating from North Carolina, USA (Mackay et al ., ), were maintained in vials and placed onto new food every 2 weeks.…”
Section: Methodsmentioning
confidence: 99%
“…Aliquots of L. lactis and P. entomophila were stored in 34.4% glycerol at −80 °C. Lactococcus lactis was plated on lysogeny broth (LB) agar and P. entomophila was plated on LB agar containing 1% milk to select for protease positive clones (Neyen et al ., ), after which, bacterial preparation and infections were carried out following Kutzer & Armitage () using a randomized block design of 60 total treatment groups (10 genotypes × 2 diets × 3 infection treatments). In each experimental replicate, we processed three flies per treatment group, giving 21 flies per genotype × diet × infection treatment, that is 1260 flies in total.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…‘resistance’), it provided the host with the ability to reduce the damage of the infection on its health, also called ‘tolerance’ (Ayres & Schneider, , ). Diet composition may affect tolerance of infection (Howick & Lazzaro, ; Kutzer & Armitage, ; Miller & Cotter, ); for example, it has been shown that yeast restriction in Drosophila flies affects tolerance specifically to one strain of bacterium in a time‐dependent manner; however, no effect on resistance was detected (Kutzer & Armitage, ).…”
Section: Introductionmentioning
confidence: 99%